If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 12 = 2(3a + -8) Reorder the terms: 12 + 6x = 2(3a + -8) Reorder the terms: 12 + 6x = 2(-8 + 3a) 12 + 6x = (-8 * 2 + 3a * 2) 12 + 6x = (-16 + 6a) Solving 12 + 6x = -16 + 6a Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 6x = -16 + -12 + 6a Combine like terms: 12 + -12 = 0 0 + 6x = -16 + -12 + 6a 6x = -16 + -12 + 6a Combine like terms: -16 + -12 = -28 6x = -28 + 6a Divide each side by '6'. x = -4.666666667 + a Simplifying x = -4.666666667 + a
| 2n^2=-10n-5 | | -1/9(x-27)+1/3=x+25 | | x^3-8x^2-9x+72=0 | | 138.24=-8(2.3p-4.4) | | [5y+(6x+3)][5y-(6+3)]= | | 8X^4-56x^3+56x^2=0 | | 2(x)-4=5-x | | 8+4(z-2)=-5z+5 | | X^2(X^2-16)-64(X^2-16)=0 | | (1/4^2)-(3/2)-(7/4) | | x(3+7)-5=5(x+4)+5 | | y=8/3*1+8 | | 3r^2-5r-2= | | 1/4^2-3/2-7/4 | | n/7+6=13 | | 4=3x-8-2(5-x) | | t^4+43t^2+42=0 | | r^2-3r+2= | | 3c-12=145c | | 3k^2+-14k+8= | | 3m^2-8m=0 | | -1.6(1+7.6r)=-90.368 | | -7/3=-7/2u-7/5 | | 3(-6+x)=4x-1/3 | | (3x+7/4)+(x+22/5)=9 | | -8*1+7y=-56 | | 5(3m+8)+8(m+4)=95 | | 9d^2+18d+8=0 | | 9a-3a=2a+24 | | 3x+7/4+x+22/5=9 | | (5x-9)(2x+3)= | | t-(9)=4 |